Post Post-Truth: Epistemologies of Disintegration and the Praxeology of Truth - Kleeberg, Bernhard (Stan Rzeczy, 2019)
Our truth culture has changed. Yet we are not living in a post-truth era but in a truth era – an observation of the ongoing debates shows a proliferation of invocations of truth. This paper argues that in order to grasp this transition, we should not refer to classical truth theories or common oppositions such as knowledge and belief, objectivity and subjectivity. Instead, we should focus on concrete practices in concrete situations: on “doing truth.” This paper introduces the concept of a “praxeology of truth,” which sets out to analyse truth by means of two parameters: “truth scenes” and “truth figures.” In suggesting that to ask about truth is to pose the question of power, it follows Michel Foucault, but it regards the invocation of truth as a technique of identity politics and truth as a social operator.